Tinjauan Hukum Pidana Islam terhadap Pembunuhan karena Kealpaan (Analisis Putusan No. 12/Pid.B/2011/Pn.Sinjai) - Muhammad, Mar’ie Ma’arif; Marpaung, Zaid Alfauza (Prodi Hukum Ekonomi Syariah (Muamalah), 2024)
The research objective was to analyse decision No. 12/Pid.B/2011/Pn.Sinjai related to manslaughter through a normative juridical approach. This research method uses a type of normative juridical research with a statutory, conceptual, and case approach, which analyses primary legal sources such as and cases, which analyses primary legal sources such as the Al-Quran, Hadith, laws and regulations, and court decisions, as well as secondary sources in the form of literature, journals, and court decisions. Secondary sources in the form of literature, journals, and other legal documents, through data collection techniques. Data collection techniques of literature study and document analysis, with qualitative and descriptive-analytical data analysis. Data analysis is qualitative and descriptive-analytical. The results showed that the application of Islamic criminal law in cases of manslaughter needs to consider aspects of the intention and negligence of the perpetrator, as well as the impact on the victim's family and society.